Outcomes of early and reversible renal impairment in patients with ST segment elevation myocardial infarction undergoing percutaneous coronary intervention. Issue 7 (October 2020) - Khoury, Shafik; Margolis, Gilad; Ravid, Dor; Rozenbaum, Zach; Keren, Gad; Shacham, Yacov
Objective: Acute kidney injury (AKI) is a frequent complication in patients with ST segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). While AKI occurring post-PCI has been well studied, the incidence and clinical significance of early renal impairment evident on hospital admission prior to PCI and which resolves towards discharge has not been investigated. Methods: We retrospectively studied 2339 STEMI patients treated with primary PCI. The incidence of renal impairment and in-hospital complications as well as short and long-term mortality were compared between patients who did not develop renal impairment, patients who developed post-PCI AKI and those who presented with renal impairment on admission but improved their renal function during hospitalization (improved renal function). Improved renal function was defined as continuous and gradual decrease of ⩾ 0.3 mg/dL in serum creatinine levels obtained at hospital admission. Results: One hundred and nineteen patients (5%) had improved renal function and 230 patients (10%) developed post-PCI AKI. When compared with patients with no renal impairment, improved renal function and post-PCI AKI were associated with more complications and adverse events during hospitalization as well as higher 30-day mortality. Long-term mortality was significantly higher among those with post-PCI AKI (63/230, 27%) following STEMI than those without renal impairment (104/1990, 5%; p <0.001), but there was no significant difference in long term mortality between patients with no renal impairment and those with improved renal function (5% vs . 7.5%, p =0.17). Conclusion: In STEMI patients undergoing primary PCI, the presence of renal impairment prior to PCI which resolves towards discharge is not uncommon and is associated with adverse short-term outcomes but better long-term outcomes compared with post-PCI AKI.